Filtration Performance of Layering Masks and Face Coverings and the Reusability of Cotton Masks after Repeated Washing and Drying - Sumit Sankhyan; Karen N. Heinselman; Peter N. Ciesielski; Teresa Barnes; Michael E. Himmel; Hannah Teed; Sameer Patel; Marina E. Vance (Aerosol and Air Quality Research)
Abstract In this study, filtration efficiency of different respirators, face masks, and a 2-ply cotton handkerchief bandana was compared for particles in the size range of 60 nm–4 µm under a “perfect fit” condition. The filtration efficiency at the most penetrating particle size of 0.3 µm on average ranged from 83–99% for N95 and KN95 respirators, 42–88% for surgical masks, 16–23% for cloth masks, and 9% for bandana. We also investigated the effects of using double surgical masks or layering a cloth mask over various surgical masks in terms of their filtration characteristics. In most of these combinations, the filtration efficiency improved by ~25% for particles 0.3–1 µm in diameter without any substantial change in the filter quality factor when compared to the highest of the individual mask results. To investigate the reusability of cotton cloth masks, 2-layer cotton fabric sample coupons were machine washed and dried for 52 cycles leading to an increase in inhalation resistance (~20 Pa) without affecting size-resolved filtration efficiency. Scanning electron microscopy revealed that washing and drying led to the gradual deconstruction of cotton fibers at the scale of several micrometers to hundreds of nanometers in the form of delamination of the fiber wall and fibrillation of the nanofiber constituents. Results indicate that cloth masks may be layered over surgical masks for additional benefits, and that cloth masks made out of cotton fabric can be washed and reused numerous times without a significant loss in filtration efficiency.